ナンキョク ニオケル ムジン カンソク 1 ムジン カンソク ソウチ ノ カイハツ ト カンソク ケッカ ノ ソクホウ - 鮎川, 勝; アユカワ, マサル; 寺井, 啓; テライ, ケイ; 勝田, 豊; カツタ, ユタカ; 吉田, 治郎; ヨシダ, ジロウ; 外谷, 健; トヤ, タケシ; 坂本, 純一; サカモト, ジュンイチ; et al. (国立極地研究所, 1979)
P(論文) 日本南極地域観測事業では国際磁気圏観測計画(1976-1978)の一環としてオーロラ・フレーアの発生機構を解明するため,東南極大陸氷床上のみずほ基地を中心とした周辺に無人による地上観測網の設置を計画した.本報告は,この計画を遂行するために必要な長期無人観測施設の開発に関して実施した基礎実験と,その結果に基づいて試作した無人観測システムの紹介および各種性能試験結果を報告する.また,1977年5月30日から8月23日までの約3ヵ月間,東南極みずほ高原付近において試作無人観測システムを用いて地磁気三成分観測に成功したので速報する.風エネルギー利用の風車発電機を初めて実用化した試作無人観測施設は,極低温環境下において正常に動作し,超高層自然現象に関する基礎的物理量である地磁気変化の量を良好に記録した. It was planned to set up several unmanned upper atmosphere observatories in the area around Mizuho Station (70°42' S, 44°20' E) in Antarctica during the period of 1976-1978 for the IMS (International Magnetospheric Study). The first unmanned observatory, situated between Mizuho and Syowa Stations in Antarctica, was set up on May 30, 1977 by the wintering party of the 18th Japanese Antarctic Research Expedition. Observation of geomasnetic variations at this observatory was carried out from May 30 to August 23, 1977. The unmanned observatory consists of the following parts. 1. Wind-driven generator Two wind-driven generators (DYNA Technology Co., model 1222H) are used for keeping batteries and instruments warm. Each generator can supply electric power of～200 W on an average when the wind blows continuously at a speed of～10 m/s. 2. Heat insulation boxes Batteries and instruments are put in two heat insulation boxes. The boxes protect the batteries and instruments from low temperature and heavy snow in Antarctica. The wall of these boxes is made of veneer, aluminium plate and styrofoam plate with a thickness of～10 cm. Using thermostats and heaters (200 W for the battery box and 100 W for the instrument box), the temperature inside the boxes can be kept from 0℃ to 10℃ near Mizuho Station throughout the year. 3. Instrumentation Fluxgate type magnetometer Component : H, D, Z components Sensitivity : 10 nT/mm on the chart record Range : ±1250 nT Power consumotion : +18 V/100 mA, -18 V/60 mA Timing : Chronometer (stability 10^8) 4. Recorder The heat pen recorder is used. The data observed at the unmanned observatory are recorded on a chart which is replaced every ...